Great Men and Women - Leslie Westbrook Leavitt 1895-1983; Peter Horne (Egypt Egyptian International Publishing-Longman, 2004)
English As a Second Language Bk
Mahatma Gandhi -- Florence Nightingale -- Abraham Lincoln -- Madame Curie -- Albert Schweitzer.
Vocabulary level: 1800 words.
Keywords: Literature (3GdCOHs; Readers -- United States; Readers; General